Meso-cenozoic tectonic evolution of the ziyun-luodian fault in SW China - Wang, Yi; Du, Wei; Wang, Yuyang; Lin, Ruiqin; Zhang, Daquan; Zhao, Fuping; Sun, Zhao; Chen, Yi; Wang, Yang (Frontiers in Earth Science, 2022)
Regional-scale fault systems are important in adjusting intracontinental deformation. Closure of the Paleo-Tethys, Paleo-Pacific subduction, and India- continent-continent collision have all interacted to shape the Meso-Cenozoic tectonics of South China. The Ziyun-Luodian fault (ZLF) straddles across the Guizhou region in southwestern China. New petrographic and structural studies were conducted to reveal the structural evolution of the ZLF and regional deformation. At least three distinct deformation events are identified within the fault zone: During the Indosinian orogeny, dextral thrusting occurred along the ZLF, accompanied by moderate regional uplift in Guizhou, as evidenced by the Upper Triassic-Lower Jurassic disconformity. The main tectonic framework across Guizhou was established during the Yanshanian orogeny. Driven by the west-dipping Paleo-Pacific subduction (Middle Jurassic-Early Cretaceous), sinistral transpression occurred along the ZLF and NE- to N-S-trending fold belts in central-eastern Guizhou, and the NW-striking folds west of the ZLF were developed in under nearly E-W-directed compression. In the late Cenozoic, the ZLF may have undergone sinistral strike-slip movement, similar to the sinistral Ailaoshan-Red River shear zone. The Ziyun-Luodian fault plays an important role in accommodating the Meso-Cenozoic regional deformation in SW South China.